2016
DOI: 10.1098/rsif.2016.0396
|View full text |Cite
|
Sign up to set email alerts
|

Structural features of reconstituted wheat wax films

Abstract: Cuticular waxes are essential for the well-being of all plants, from controlling the transport of water and nutrients across the plant surface to protecting them against external environmental attacks. Despite their significance, our current understanding regarding the structure and function of the wax film is limited. In this work, we have formed representative reconstituted wax film models of controlled thicknesses that facilitated an ex vivo study of plant cuticular wax film properties by neutron reflection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 39 publications
5
35
0
Order By: Relevance
“…The process was programmed to run for 20 s at 3000 rpm, with an initial acceleration of 1000 rpm for 3 s. This coating procedure for forming reconstituted wax films was discussed in the previous study and was found to generate reproducible uniform films within the thickness range of cuticular wax films found in cereal crops. 22 For SE measurements, Si wafers (2 cm × 2 cm) were spin coated in the fashion similar to the Si blocks used for NR, with 200 μl of solution deposited onto the surface prior to coating.…”
Section: Sample Preparation and Thin Film Coatingmentioning
confidence: 99%
See 4 more Smart Citations
“…The process was programmed to run for 20 s at 3000 rpm, with an initial acceleration of 1000 rpm for 3 s. This coating procedure for forming reconstituted wax films was discussed in the previous study and was found to generate reproducible uniform films within the thickness range of cuticular wax films found in cereal crops. 22 For SE measurements, Si wafers (2 cm × 2 cm) were spin coated in the fashion similar to the Si blocks used for NR, with 200 μl of solution deposited onto the surface prior to coating.…”
Section: Sample Preparation and Thin Film Coatingmentioning
confidence: 99%
“…[35][36][37][38] The reflectivity profile which represents the structural distribution of an interfacial material is described by the Abeles layer model through a discrete series of homogeneous slabs each characterized by their SLD and thickness. 28,30 In this study, the general solution to the optical matrix used to describe any standard stratified layer 22,23 was modified to more accurately describe the observed interfacial roughness and density variations of the reconstituted cuticular wax films. It has been shown that the material's volume fraction and SLD distribution profiles could be adequately described using a 2-layer model based on the error function model developed by Hughes.…”
Section: Neutron Reflection (Nr)mentioning
confidence: 99%
See 3 more Smart Citations